2011
DOI: 10.1097/ipc.0b013e3181fc6e7c
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulation and Venous Thromboembolism Due to Acute Epstein-Barr Virus Infection

Abstract: We describe a case of a healthy 61-year-old man who developed disseminated intravascular coagulation and venous thromboembolism secondary to acute Epstein-Barr virus (EBV) infection. The EBV was confirmed via serology and polymerase chain reaction. Although more common in children and young adults, acute EBV infection may also occur in middle-age and older adults and should be considered as a differential diagnosis in every patient presenting with disseminated intravascular coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 7 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…Second, EBV-induced proinflammatory cytokines during inflammation play an important role in differential effects on the coagulation and fibrinolysis pathway. This may result in activation of the procoagulant pathway with subsequent thrombosis as reported previously (24) or an acquired hyperfibrinolytic state. This is the first report of a life-threatening, hemorrhagic diathesis in children with EBV-associated T-cell LPD, including their ICU course and outcome.…”
Section: Discussionmentioning
confidence: 85%
“…Second, EBV-induced proinflammatory cytokines during inflammation play an important role in differential effects on the coagulation and fibrinolysis pathway. This may result in activation of the procoagulant pathway with subsequent thrombosis as reported previously (24) or an acquired hyperfibrinolytic state. This is the first report of a life-threatening, hemorrhagic diathesis in children with EBV-associated T-cell LPD, including their ICU course and outcome.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, some of these patients were found to have elevated levels of aPL, a variable identified as favouring blood clot formation, as previously stated [95,96]. Although poorly understood, to the best of our knowledge, venous thrombosis in EBV patients might be related to oxidativeinducing endothelial cell injury and inflammation, with the consequent secretion of TF [69,87,95,96].…”
Section: Reviewmentioning
confidence: 86%
“…Data is still lacking regarding the impact of EBV infection on the development of thromboembolic events [ 69 ]. Despite being seldom reported mostly in immunocompromised patients, according to a few case-reports studies, this cardiovascular disease has also been identified in immunocompetent patients suffering from an acute EBV infection, which contributed to the worsening of their clinical outcome [ 69 , 87 , 95 98 ]. Interestingly, some of these patients were found to have elevated levels of aPL, a variable identified as favouring blood clot formation, as previously stated [ 95 , 96 ].…”
Section: Viral Carcinogenesis and Vte Incidencementioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 VTE is also one of the hematological complications of infectious mononucleosis, although uncommon in immunocompetent patients. 13 In children with acute Varicella zoster virus (VZV) infection, PE and DVT have been frequently reported. 14 It can also cause stroke in children who suffer from chickenpox.…”
Section: Introductionmentioning
confidence: 99%